Investigating the Structural, Spectroscopic, and Electrochemical Properties of [Fe{(EPiPr2)2N}2] (E = S, Se) and the Formation of Iron Selenides by Chemical Vapor Deposition. Issue 35 (26th October 2016) - Levesanos, Nikolaos; Liyanage, Wipula P. R.; Ferentinos, Eleftherios; Raptopoulos, Grigorios; Paraskevopoulou, Patrina; Sanakis, Yiannis; Choudhury, Amitava; Stavropoulos, Pericles; Nath, Manashi; Kyritsis, Panayotis
Abstract : The anionic L = [(EP i Pr2 )2 N] – (E = S, Se) form of the dichalcogenidoimidodiphosphinato‐type ligands containing i Pr peripheral groups has been shown previously to afford tetrahedral [M II L2 ] complexes (E = S, M = Mn, Co, Ni, Zn; E = Se, M = Co, Ni, Zn). The syntheses of the analogous [FeL2 ] complexes [E = S (1 ), Se (2 )] were performed in this work through metathesis reactions between FeCl2 and the corresponding KL salts. For both1 and2, X‐ray crystallography revealed two distinct molecules in the asymmetric unit. Complexes1 and2 are isostructural and exhibit P–E and P–N bond‐length differences compared with those of the free ligands, and these differences are translated into shifts of the corresponding IR bands. Cyclic voltammetry studies showed that the Fe II → Fe III oxidation in2 occurs at a lower potential than that of1 . The zero‐field Mössbauer spectra of the two complexes are quite similar and provide evidence of similar S = 2 electronic structures. The observation of crystallographically distinct Fe II E4 sites for both1 and2 is also revealed in the corresponding Mössbauer spectra. Complex2 was employed as a single‐source precursor in catalyst‐aided chemical vapor deposition experiments, which afforded the iron selenides FeSe and Fe3 Se4 . Abstract : The structural, spectroscopic, and electrochemical characterization of [Fe{(EP i Pr2 )2 N}2 ] [E = S (1 ), Se (2 )] is reported. Chemical vapor deposition (CVD) experiments with2 afford iron selenides, including FeSe.